An evaluation of the biological activity of zinc oxide nanoparticles fabricated from aqueous bark extracts of Acacia nilotica - Manoharan Janani; Thandapani Gomathi; Ranganathan Babujanarthanam; K. Kaviyarasu (Journal of King Saud University: Science, 2023)
The phyto nanotechnology strategy was executed for the genesis of zinc oxide nanoparticles by applying bark aqueous extract of Acacia nilotica (AN-ZnO NPs). The AN-ZnO NPs emergence was substantiated through a distinct peak at 350 nm in the ultraviolet–visible spectroscopy. The fourier transform infrared spectroscopy exposed the phyto-organic moieties engaged as reduction and stabilization factors in fabricating nanoparticles. The crystalline trait, elemental proportions, spherical and hexagonal geometry of AN-ZnO NPs was witnessed by X-ray diffraction, energy-dispersive X-ray analysis and scanning electron microscopy. The high-resolution transmission electron microscopic technique provided the average size of 35 nm. AN-ZnO NPs presented larger inhibition zone against Candida albicans (22.7 ± 0.32 mm) at 40 µg/mL as an effectual fungicidal agent. Execution of in vitro antiradical scavenging assay of AN-ZnO NPs applying 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO), hydroxyl radical (OH–), 2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) displayed radical scavenging trait with the minimum inhibitory concentration (IC50) of 34.54 µg/mL, 38.0 µg/mL, 41.34 µg/mL, and 35.41 µg/mL, respectively. Cytotoxic feature against MCF-7 cell line was in a dose-manner with IC50 value of 37.15 µg/mL in addition to apoptotic proteins expressions were displayed by AN-ZnO NPs. An appreciable larvicidal role of AN-ZnO NPs was rendered against Anopheles stephensi with LD50 (0.31 ppm) and LD90 (0.59 ppm), besides acetylcholinesterase inhibition. Further, biofilm origination was remarkably ceased by the Staphylococcus aureus and Klebsiella pneumoniae, respectively. All our experimented reports on AN-ZnO NPs attested the credible applicability of ZnO NPs in biomedical care for health troubles.